Climate change impacts on yield, evapotranspiration and nitrogen uptake in irrigated maize (Zea mays)–wheat (Triticum aestivum) cropping system: a simulation analysis - KAUR, HARSIMRAN; JALOTA, S K; KANWAR, RAMESH; VASHISHT, BHARAT BHUSHAN (The Indian Journal of Agricultural Sciences, 2012)
Considering the present trends of global climate change, atmospheric CO2 and temperature levels are likely to increase in future, which will affect yields, water and nitrogen requirements of the crops in a given region. The present study concerns quantification of direct and interactive effects of the elevated CO2 (from 350 to 700ppm) and temperature (from existing to 3ºC higher) on yield, nitrogen uptake and evapotranspiration (ET) of optimally irrigated (IW/Pan E ratio=0.9) and fertilized (120 kg/ha) maize–wheat cropping system on texturally variable soils. IW and Pan E are amounts of irrigation water and open pan evaporation, respectively. Averaged over 30 years simulations with the already calibrated and validated CropSyst model showed that by increasing CO2 concentration from 350 to 700ppm in maize and wheat, yields were increased by 17 and 57%, ET decreased by 14 and 3 mm; and nitrogen uptake increased by 12 and 44 kg/ha respectively. The effect of increased CO2 was more in wheat (C3 plant) than that in maize (C4). At 350ppm CO2 with temperature 3°C higher than the existing in maize and wheat crops, crop durations of maize and wheat were shortened by 12 and 23 days, ET decreased by 30 and 50 mm, nitrogen uptake decreased by 31 and 27 kg/ha and subsequently yields were reduced by 37 and 15%, respectively. The interaction of CO2 and temperature indicates that even 700ppm level of CO2 was not able to maintain the existing maize yield beyond one degree increase in temperature. In case of wheat, yield levels were well maintained at 700ppm level of CO2 even at higher level of temperature (3°C). Increased levels of irrigation (IW/Pan E ratio=1.25) and nitrogen (150 and 180 kg/ha) were not able to outweigh the negative effect due to increased temperature than the existing in this cropping system.